Growth pattern of friable calluses from leaves of Capsicum annuum var. annuum cv. Iberaba Jalapeño (Revista Ciência Agronômica, 2017)
The genus Capsicum belongs to the Solanaceae botanical family and is notable for the production of secondarymetabolites of medicinal and economical importance. In vitro methods have been successfully utilized for the large scaleproduction of plant secondary metabolites. The objective of this study was to establish a protocol for callus induction fromleaves, nodal and internodal segments of the cultivar C. annuum var. annuum cv. Iberaba Jalapeño, and to determine the growthpattern of the calluses, aiming at the identification of the deceleration phase, when the callus cells must be subcultured for theestablishment of cell suspensions and the production of secondary metabolites. The explants were inoculated into a mediumsupplemented with BA and 2,4-D in factorial combination. Percentage of callus induction and the explant area covered bycallus cells (ACCC) were evaluated. The procedures that resulted in higher proliferation of callus cells were repeated in orderto determine the growth curve of the calluses. The highest callus induction percentage and ACCC were observed with thecombination of 2.22 µM BA + 18.10 µM 2,4-D for leaf and internodal explants and 2.22 µM BA + 9.05 µM 2,4-D for nodalexplants. The calluses produced were friable and whitish, and their growth pattern followed a sigmoid shape. The decelerationphase started on the 31st day of cultivation for leaf explants, on the 26th for internodal explants, and on the 29th day for nodalexplants.